Effects of El Niño on the dynamics of Lake Alchichica, central Mexico - Alfonso Lugo; Javier Alcocer (Geofísica Internacional, 2003)
Lake Alchichica is a deep, warm-monomictic lake in Puebla State, central Mexico. Water temperature, dissolved oxygen and chlorophyll a annual concentration patterns are compared under ENSO and non-ENSO conditions. The effects of ENSO on tropical Lake Alchichica lead to extreme values above or below the long-term averages in the physics, chemistry and biology of the lake. We find a narrower and slightly colder hypolimnion, larger thermal changes along the thermocline, a shallower thermocline, warmer epilimnion, later start of the hypoxic/anoxic condition of the hypolimnion, thinner hypolimnetic anoxic layer, and modest spring cyanobacteria bloom.